2020
DOI: 10.1371/journal.pgen.1008975
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging a gain-of-function allele of Caenorhabditis elegans paqr-1 to elucidate membrane homeostasis by PAQR proteins

Abstract: The C. elegans proteins PAQR-2 (a homolog of the human seven-transmembrane domain AdipoR1 and AdipoR2 proteins) and IGLR-2 (a homolog of the mammalian LRIG proteins characterized by a single transmembrane domain and the presence of immunoglobulin domains and leucine-rich repeats in their extracellular portion) form a complex that protects against plasma membrane rigidification by promoting the expression of fatty acid desaturases and the incorporation of polyunsaturated fatty acids into phospholipids, hence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 88 publications
1
15
0
Order By: Relevance
“…There are 5 PAQR proteins encoded by the C. elegans genome, two of which are clear ADIPOR homologs and are named PAQR-1 and PAQR-2 (there are no adiponectin homologs in C. elegans) [25]. Mutants lacking PAQR-1 have no obvious phenotypes, though they enhance the phenotypes of worms lacking PAQR-2, indicating redundancy [25,26]. Worms lacking PAQR-2 have a deformed tail tip, impaired autophagy, reduced life span, brood size and locomotion, and are cold-and SFA-intolerant because both conditions promote membrane rigidification [25,[27][28][29][30][31].…”
Section: Lessons From C Elegansmentioning
confidence: 99%
See 2 more Smart Citations
“…There are 5 PAQR proteins encoded by the C. elegans genome, two of which are clear ADIPOR homologs and are named PAQR-1 and PAQR-2 (there are no adiponectin homologs in C. elegans) [25]. Mutants lacking PAQR-1 have no obvious phenotypes, though they enhance the phenotypes of worms lacking PAQR-2, indicating redundancy [25,26]. Worms lacking PAQR-2 have a deformed tail tip, impaired autophagy, reduced life span, brood size and locomotion, and are cold-and SFA-intolerant because both conditions promote membrane rigidification [25,[27][28][29][30][31].…”
Section: Lessons From C Elegansmentioning
confidence: 99%
“…Bifluorescence complementation (BiFC) and fluorescence resonance energy transfer (FRET) studies have shown that IGLR-2 localizes to the plasma membrane where it interacts in a membrane rigidity-dependent manner with PAQR-2 [28,37]. Additionally, structurefunction studies indicate that the two proteins interact via their transmembrane domains and, more speculatively, that IGLR-2 may help displace the cytoplasmic PAQR-2 domain to facilitate access of substrates to the active site [26,37]. Note also that IGLR-2 is not required for PAQR-1 function, suggesting that PAQR-1 either has a basal constitutive activity or is regulated via a separate mechanism [26].…”
Section: Lessons From C Elegansmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative way to protect WT cells against overwhelming amounts of PA is by over-expressing AdipoR1/2 31 , 36 . AdipoR1/2 contain a Zn 2+ ion inside the catalytic domain which is essential for their ceramidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…pIREShyg2-HA-hAdipoR2-cMYC construct was described in (Busayavalasa et al, 2020). pIREShyg2-HA-hAdipoR2-cMYC(H348A) construct was generated using PCR-based mutagenesis (Q5-site-directed mutagenesis kit, New England Biolabs) with the following primers: 5'-gctcagctgtttcatatctttg-3' and 5'-agagtgaaaccagatgtcac-3'.…”
Section: Plasmids For Hek293 Cells and Transfectionmentioning
confidence: 99%